Permeability and swell testing of selected South African bentonites - Orsmond, Wyatt (University of Cape Town, 2016)
Bibliography: pages 141-144. === Bentonite, a natural clay composed predominately of montmorillonite has become a very useful product in Civil Engineering due to its extremely low permeability and high swell potential. Bentonite has been used extensively in countries like the United States of America, Canada and Europe as an impervious liner in dams, landfill sites, retention ponds etc. where it is used in its pure form and as a composite material mixed with soil. Bentonite liners are rapidly gaining interest in many other countries including Southern Africa. Bentonite is found world wide, and in South Africa (RSA) there are three deposits presently being mined namely Heidelburg (Western Cape), Koppies (Orange Free State) and Plettenberg Bay (Eastern Cape). The bentonite from each of these deposits are called Culseal I Culbond, Koppies and Plett respectively. They all vary with regard to chemical composition and little is known about there engineering properties. The aim of this research is to provide information both general and with regard to Civil Engineering on the bentonites presently being mined in South Africa to facilitate design and future research in this field. The triple layer crystalline sheets which make up a bentonite particle are held together by weak forces and exchangeable cations (which dictate the bentonite type). When brought into contact with water, the water is drawn onto the sheets to balance the charges forcing the layers apart resulting in swelling of up to 15 times the original particle thickness. This swollen, hydrated bentonite is almost impervious.